2019
DOI: 10.3390/w11061127
|View full text |Cite
|
Sign up to set email alerts
|

Community Assembly Mechanisms Underlying the Core and Random Bacterioplankton and Microeukaryotes in a River–Reservoir System

Abstract: Whether bacterioplankton are assembled in the same way as microeukaryotes is a key question that has been answered only partially in microbial ecology. In particular, relating distribution patterns to the underlying ecological processes for plankton communities in highly dynamic ecosystems, such as river–reservoirs subjected to anthropogenic impacts, remains largely unstudied. Here, we analyzed taxonomic distribution patterns, and unraveled community assembly processes underlying the core and random bacteriopl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(17 citation statements)
references
References 60 publications
3
14
0
Order By: Relevance
“…Significant distance-decay patterns of bacteria and/or microeukaryotes have been found in rivers ( 12 , 13 ), lakes ( 9 , 14 ), intertidal zones ( 15 ), coastal seas ( 8 , 16 ), and open oceans ( 16 , 17 ). The underling mechanisms responsible for distance-decay patterns have been shown to differ between domains and between ecosystems ( 8 , 13 , 15 ). The fact that environmental factors varied spatially in the TNPO during our study ( Fig.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Significant distance-decay patterns of bacteria and/or microeukaryotes have been found in rivers ( 12 , 13 ), lakes ( 9 , 14 ), intertidal zones ( 15 ), coastal seas ( 8 , 16 ), and open oceans ( 16 , 17 ). The underling mechanisms responsible for distance-decay patterns have been shown to differ between domains and between ecosystems ( 8 , 13 , 15 ). The fact that environmental factors varied spatially in the TNPO during our study ( Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Studies of marine microbial biogeography have benefited greatly from the rapid progress that has been made in genomic sequencing and theoretical microbial ecology ( 11 ). Among the various spatial distribution patterns (e.g., latitudinal diversity patterns and taxa-area relationships), distance-decay patterns have frequently been reported based on studies of communities of bacteria and microeukaryotes in a variety of aquatic habitats, including rivers ( 12 , 13 ), lakes ( 9 , 14 ), intertidal zones ( 15 ), coastal ocean ( 8 , 16 ), and open ocean ( 16 , 17 ). However, there have been few studies of microbial biogeographic patterns in oligotrophic marine waters, especially at the trans-basin scale ( 17 ).…”
Section: Introductionmentioning
confidence: 99%
“…The |βNTI|<2 and RC bray <−0.95 or the |βNTI|<2 and RC bray ≥0.95 RCbray were identified as homogenizing dispersal and dispersal limitation, respectively. When the |βNTI|<2 and |RC bray |<0.95 were identified as “Undominated” ( Dini-Andreote et al, 2015 ; Stegen et al, 2015 ; Isabwe et al, 2019 ). To demonstrate which process contributed more to the DDR slopes between the core and satellite sub-communities, samples controlled by dispersal limitation and heterogeneous selection were separately extracted from both sub-communities according to the results of Stegen’s null model.…”
Section: Methodsmentioning
confidence: 99%
“…These highly dynamic landscapes suffer from plant biomass destruction by stochastic disturbances in addition to large variation in resource availability over a short period of time; processes that may break established environment–plant–ecosystem relationships (Kleyer et al 2014). Studies on rivers and wetlands found that neutral processes and dispersal limitation better explain species diversity in highly dynamic ecosystems than environmental filtering (Isabwe et al 2019, Schöpke et al 2019).…”
Section: Introductionmentioning
confidence: 99%